Rancang Bangun Modul IoT untuk Pembelajaran Dasar di Laboratorium di Jurusan Teknik Elektro Universitas Lampung - A Anizar; Abdurachman Effendi; Perdana A Nugraha; Muhamad R Sidiq; Nadia Salsabila (Jurnal Pengelolaan Laboratorium Pendidikan, 2022)
The employment sector is the one that has been hit the worst by the consequences of Revolution 4.0 in Indonesia. The Internet of Things is one area that human resources, particularly students in the Electrical Engineering Department, must improve (IoT). As a result, IoT learning media was developed in the laboratory, where the current IoT modules are insufficient. The goal of this research is to provide students a fundamental understanding of the Internet of Things. Arduino and ESP8266 are used in this IoT module. The Blynk and ThinkSpeak platforms are used to connect to an internet network based on web services. In this module, you can perform three different types of experiments. The first is the ThingSpeak Application for Temperature and Humidity Monitoring. The temperature in the room was 23°C, with a humidity level of 56%. The second method is to use the Blynk application to measure distance using an ultrasonic sensor. The comparison of measurements on the LCD and the Blynk application yielded results that were consistent with measurements taken using a ruler. The third option is to use the Blynk App to control water volume. As an automatic switch on the tank, a relay module is used in this experiment. The pump will turn on when the water volume is less than 100 liters and turn off when the water volume reaches 265 liters. Finally, this module can be used as a basic learning materials in the Laboratory of the Department of Electrical Engineering, Faculty of Engineering, University of Lampung.